STEM-Based Assessment in Chemistry Education: A Systematic Literature Review of Its Design and Implementation in Secondary Schools - Ningrum, Sinta Ayu; Nahadi, Nahadi (Pendidikan Kimia FKIP Universitas Jambi, 2026)
This study aims to analyze the design and implementation of STEM-based assessment in secondary school chemistry education through a Systematic Literature Review (SLR). The review follows PRISMA 2020 guidelines and examines 23 peer-reviewed articles published between 2021 and 2026, sourced from Scopus and Crossref databases. The findings indicate that STEM-based assessment designs are predominantly developed using project-based, problem-based, performance, and portfolio approaches, supported by various instruments such as e-portfolios, laboratory activities, e-modules, and test-based assessments. These designs primarily focus on measuring higher-order thinking skills, including critical thinking, creativity, problem-solving, and scientific literacy. In terms of implementation, STEM-based assessment is generally integrated into learning activities such as projects, laboratory work, and digital-based instruction, reflecting a shift toward more authentic and process-oriented evaluation practices. However, several challenges remain, including the lack of standardized assessment frameworks, uneven integration of STEM components, particularly in the engineering aspect, and limited teacher readiness in designing and implementing such assessments. These findings highlight the need for more comprehensive and standardized STEM-based assessment models, as well as continuous professional development to support effective implementation in chemistry education.